Purification and characterization of cytidine 5'-triphosphate:cytidine 5'-monophosphate-3-deoxy-D-manno-octulosonate cytidylyltransferase. - Ray, P H (1981)
Cytidine 5'-triphosphate:cytidine 5'-monophosphate-3-deoxy-D-manno-octulosonate cytidylyltransferase (CMP-KDO synthetase) was purified 2,300-fold from frozen Escherichia coli B cells. The enzyme catalyzed the formation of CMP-KDO, a very labile product, from CTP and KDO. No other sugar tested could replace KDO as an alternate substrate. Uridine 5'-triphosphate at pH 9.5 and deoxycytidine 5'-triphosphate at pH 8.0 and 9.5 could be used as alternate substrates in place of CTP. CMP-KDO synthetase required Mg2+ at a concentration of 10.0 mM for optimal activity. The pH optimum was determined to be between 9.6 and 9.3 in tris(hydroxymethyl)aminomethane-acetate or sodium-glycine buffer. This enzyme had an isoelectric point between pH 4.15 and 4.4 and appeared to be a single polypeptide chain with a molecular weight of 36,000 to 40,000. The apparent Km values for CTP and KDO in the presence of 10.0 mM Mg2+ were determined to be 2.0 X 10(-4) and 2.9 X 10(-4) M, respectively, at pH 9.5. Uridine 5'-triphosphate and deoxycytidine 5'-triphosphate had apparent Km values of 8.8 X 10(-4) and 3.4 X 10(-4) M. respectively, at pH 9.5.